Transformation of Muslim behaviour towards sustainable environment: perspectives of non-governmental organisations in Klang Valley - Mashitoh Yaacob,; Zubaidah Mohd Nasir,; W. Syairah Hazwani W. Petera,; Hassan Basri,; Ibnor Azli Ibrahim,; Mohd Yusof Othman,; Mohd Izhar Ariff Mohd Kashim,; Azami Zaharim,; Mazlin Mokhtar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Man cannot depend solely on science and technology to solve environmental problems. In fact, scholars and environmentalists have observed that some of the causes of environmental deterioration are rooted in science and technology. It is clear that environmental problems need ethical solution. However, environmentally ethical behaviour (EEB) is often overlooked in the life of a Muslim. This behaviour is important, particularly, to ensure the future of civilization of the Islamic world and, generally, civilization as a whole. Given the fact that non-governmental organisations (NGOs) are more sensitive to the transformation of public behaviour compared to other groups, this article discusses the perspectives of Malaysian NGOs on the transformation of Muslim EEB in Malaysia in three aspects: (a) The type of EEB practiced by Muslims in Malaysia; (b) The transformation process of EEB experienced by Muslims in Malaysia; and (c) Whether or not the transformation of EEB of Muslims in Malaysia is motivated by the values advocated by Islam. The research adopted a qualitative research method of data collection, i.e., focus group discussions (FGDs). FGD’s results illustrated that: (a) Pre-cycling, reusing and recycling are the common types of EEB practiced by Muslims in Malaysia; (b) The transformation process of EEB experienced by Muslims in Malaysia is not accelerating at the speed that we hoped for; and (c) The transformation of EEB of Muslims in Malaysia is motivated more by economic and social factors as well as level of education and regulation enforcement compared to the values advocated by Islam.